2006
DOI: 10.1002/jnr.20824
|View full text |Cite
|
Sign up to set email alerts
|

Chronic vitamin D3 treatment protects against neurotoxicity by glutamate in association with upregulation of vitamin D receptor mRNA expression in cultured rat cortical neurons

Abstract: The vitamin D receptor (VDR) is believed to mediate different biologic actions of vitamin D3, an active metabolite of vitamin D, through regulation of gene expression after binding to specific DNA-response element (VDRE) on target genes. To further understand roles of both vitamin D3 and VDR in the central nervous system, we examined VDRE binding in nuclear extracts prepared from discrete rat brain regions and cultured rat cortical neurons by electrophoretic mobility shift assay. The highest activity of VDRE b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
87
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(96 citation statements)
references
References 27 publications
1
87
0
4
Order By: Relevance
“…It was suggested that vitamin D exerts its neuroprotective effect through downregulation of L-type calcium channel expression or upregulation of vitamin D receptor (VDR) expression [11]. Thus, vitamin D deficiency has been identified as a factor associated with increased risk for development of neurological diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that vitamin D exerts its neuroprotective effect through downregulation of L-type calcium channel expression or upregulation of vitamin D receptor (VDR) expression [11]. Thus, vitamin D deficiency has been identified as a factor associated with increased risk for development of neurological diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D may affect neuronal plasticity processes and increase neurite outgrowth when added to cultured hippocampal cells (28). It has been revealed that vitamin D upregulates the expression of microtubule-associated protein-2 and growth-associated protein-43 in cultured cortical neurons (32). Maternal hypovitaminosis D decreases the expression of proteins involved in cytoskeleton maintenance, including neurofilaments, tubulin, actin and glial fibrillary acidic protein (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…The detrimental effects of excessive Ca 2+ on memory formation and cognitive functioning are widely acknowledged (46)(47)(48)(49). Administration of vitamin D or its metabolites may decrease neuronal death in rat hippocampal cultures, elicited by Ca 2+ -mediated neurotoxicity through the downregulation of LVSCC and increased VDR levels (26,32).…”
Section: Discussionmentioning
confidence: 99%
“…A variable pattern of VDR staining was seen in the amygdala. Taniura et al [169] demonstrated very high activity for vitamin D specific DNA-response element (VDRE) binding in the cerebellum, an area of the brain most severely affected in autism. They suggest a trophic role for vitamin D3 in the CNS and also noted that the neurohormone significantly protected cultured cortical neurons from glutamate excitotoxicity.…”
Section: Prevention and Amelioration Of Asdmentioning
confidence: 99%